Enhancement of lipase activity for the oily wastewater treatment by an electrostimulation process. Issue 116 (16th December 2016) - Adibzadeh, A.; Rezaee, A.; Salehi, Z.
Abstract : The efficacy of electrostimulation on bacterial lipase activity and COD removal was studied using a laboratory bioelectrochemical system. Abstract : The efficacy of electrostimulation on bacterial lipase activity and COD removal was studied using a laboratory bioelectrochemical system. A stainless steel mesh was used as both anode and cathode. The results showed that the maximum lipase activity obtained was 38 Umol mL −1 at an applied current of 1 mA and a COD concentration of 1100 mg L −1 . COD removal efficiency decreased when the reaction time was shorter. Moreover, the lipase activity increased when current was increased to 10 mA. The optimum pH for the lipase activity was 7.0, and when the pH value was increased to 9.0, the lipase activity decreased. The kinetics for the COD removal were specified based on the data for the decomposition time, which was the reaction time required to attain a COD removal of more than 99% in the feed wastewater. Linear plotting showed that the experimental data fitted very well with that of the Michaelis–Menten model ( R 2 = 0.9955). This shows that a suitable applied current could stimulate and improve the lipase activity. Therefore, this study provides useful information to correct the bioelectrochemical system designs and increase the removal efficiency of dissolved oils.